Spatial Mapping of Periodontal Disease in Primary Health Care of Genuk, Indonesia: Geospatial Information Systems Analysis - Gyan Shirin Ebadi Kayla Az Zahra; Diki Bima Prasetio; Hayyu Failasufa (Indonesian Journal of Global Health Research, 2025)
Periodontal disease is a disease characterized by inflammation and degeneration of the soft tissues and bone supporting the teeth. The accumulation of plaque, tartar and calculus bacteria on the teeth is a local factor and the main cause of periodontal disease. Environmental factors also indirectly affect the incidence of periodontal disease. Geographic information systems (GIS) are tools used to work with data that has information about location. The research method used is descriptive observational with cross sectional design to determine the spread of periodontal disease based on determinant factors in Genuk Community Health Center Working Area, Semarang City. The study population comprised individuals diagnosed with periodontal disease at the Genuk Community Health Center. A simple random sampling technique, a probability sampling method, was used. The sample size, determined using the Slovin Formula, consisted of 92 respondents. Data collection involved questionnaires completed by participants and direct observation of oral hygiene. Spatial data, specifically coordinates of periodontal disease locations, were recorded using ArcGIS Earth Geographic Information System software. In light of the fact that no analogous studies have been carried out in this area, this research is projected to yield beneficial information regarding the dissemination of periodontal disease according to its determinants within the service area of the Genuk Community Health Center. The results of the research show that the spread of periodontal disease in the Genuk Community Health Center working area is uneven, with Genuksari Village having the highest number of cases and Terboyo Kulon Village having the lowest number of cases with majority of respondents consume artesian water as their main water source.